RANCANG BANGUN ALAT PENETAS TELUR AYAM BERBASIS MIKROKONTROLER - Tamam, Muhammad Taufiq; Taufiq, Arif Johar; B., Gunawan P. (UMP, 2010)
Has done research on chicken egg incubator device based on microcontroller. This tool works by controlling the temperature in the hatching room, which is between 36 Â°C to 39 Â°C. Based on test results, the tool is able to hatch chicken eggs with a success rate to 60%.Key word: chicken egg incubator, microcontroller